An Estimation of Buyer Fatigue by Examination Energy Consumed in the Purchase Process - Dmytro PRUNENKO; Iryna BALANDINA; Iryna POLCHANINOVA; Mykola PYSAREVSKYI; Iryna PYSAREVA; Olha RADIONOVA; Andrii GALKIN (Communications of International Proceedings, 2020)
Consumer in the process of purchases requires new system approaches to measure fatigue. Neuromarketing is an innovative direction to improve the effectiveness of the company's marketing communications (primarily merchandising and advertising), by influencing the behaviour of a person as a potential buyer, taking into account the neurophysiological features of the process of making a purchase decision. The study of buyer fatigue by examination energy consumed in the monitoring purchase process and the development of recommendations for improving the activities of retailer to reducing the fatigue on their basis is an actual topic of research that is not fully disclosed. The research is aimed at assessing the impact of the elements of the process of purchases on the buyer fatigue at urban retailers. An experimental designed method to estimate the effect of the shopping environment on energy fatigue consumed in purchase process is presented. The result can improve the quality of shopping services on decreasing average fatigue level (energy cost) in store.
Keywords: Energy; Buyer; Total Energy Expenditure; behavior; marketing.